2013
DOI: 10.1212/01.wnl.0000436938.70528.4a
|View full text |Cite
|
Sign up to set email alerts
|

Practice variability in brain death determination

Abstract: Objective: To characterize the present state of brain death (BD) determination in actual practice relative to contemporary American Academy of Neurology (AAN) guidelines. Methods:We reviewed the charts of all adult (16 years and older) BD organ donors during 2011 from 68 heterogeneous hospitals in the Midwest United States. Data were collected across 5 categories: guideline performance, preclinical testing, clinical examination, apnea testing, and use of ancillary tests. Practice within categories and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 15 publications
0
50
0
3
Order By: Relevance
“…1 The data are not sufficient to draw this conclusion. Age at onset studies conducted in a single disease group cannot indicate associations with risk factors because the age at onset depends on the age distributions of the groups from which the participants are selected in the source population.…”
Section: Bilingualism Delays Age At Onset Of Dementia Independent Ofmentioning
confidence: 93%
See 1 more Smart Citation
“…1 The data are not sufficient to draw this conclusion. Age at onset studies conducted in a single disease group cannot indicate associations with risk factors because the age at onset depends on the age distributions of the groups from which the participants are selected in the source population.…”
Section: Bilingualism Delays Age At Onset Of Dementia Independent Ofmentioning
confidence: 93%
“…Noam Y. Stadlan, Skokie, IL: Shappell et al 1 highlighted the problems concerning determinations of death. If documentation reflects reality, some patients were declared dead with neither an apnea test nor confirmatory testing.…”
Section: Practice Variability In Brain Death Determination: a Call Tomentioning
confidence: 99%
“…A recent examination of 508 major U.S. hospitals demonstrated wide variability in brain death policies, which were not fully congruent with contemporary practice parameters (26). A chart review of 226 brain-dead organ donors at 68 heterogeneous hospitals in the Midwest United States revealed that documentation was often incomplete, likely reflecting actual variability in practice (58). Adherence to contemporary AAN guidelines was followed strictly in only 45% of patient records and loosely in 37%.…”
Section: The Evaluation Of Brain Death the Clinical Examinationmentioning
confidence: 99%
“…Authors Respond: Daryl Story, MD, Stephen Winter, MD: In an era where there is still wide variability in the process for determining brain death, 7 we welcome the comments our report has produced.…”
mentioning
confidence: 97%